Rent-sharing under different bargaining regimes: evidence from linked employer-employee data - Michael Rusinek; François Rycx (Institute for the Study of Labor (IZA), 2008)
In many European countries, the majority of workers have their wages directly defined by industry-level agreements. In addition, for some workers, industry agreements are complemented by firm-specific agreements. Yet, the relative importance of firm and industry agreements (in other words, the degree of centralization) differs drastically across industries. The authors of this paper use unique linked employer-employee data from a 2003 survey in Belgium to examine how these bargaining features affect the extent of rent-sharing. Their results show that there is substantially more rent-sharing in decentralized than in centralized industries, even when controlling for the endogeneity of profits, for heterogeneity among workers and firms and for differences in characteristics between bargaining regimes. Moreover, in centralized industries, rent-sharing is found only for workers that are covered by a firm agreement. Finally, results indicate that within decentralized industries, both firm and industry bargaining generate rent-sharing to the same extent.
urn:nbn:de:101:1-2008032089
Keywords: J31; 330; Rent-sharing; collective bargaining; propensity score matching; Tarifpolitik; Lohnverhandlungen; Betriebsvereinbarung; Vergleich; Lohnbildung; Rententheorie; Belgien